High-Gain Observer in Fuel Cell and Cascaded DC-DC Boost Converter System - Nady Soukaina; El Fadil Hassan; Lassioui Abdellah; El Asri Yassine; Hasni Anwar (E3S Web of Conferences)
In this study, we propose using a high-gain observer (HGO) in fuel cell systems and the FC-cascade boost converter to achieve precise state estimation and improve control accuracy. The HGO offers significant advantages, including robustness to disturbances, simplicity of design, and reduced dependency on costly sensors, thereby enhancing system performance and reducing operational costs. Our results demonstrate the superior accuracy and reliability of this approach, confirming its potential as a promising solution for fuel cell applications.